Impacts of black carbon on the formation of advection–radiation fog during a haze pollution episode in eastern China - Q. Ding; Q. Ding; Q. Ding; J. Sun; J. Sun; J. Sun; X. Huang; X. Huang; X. Huang; A. Ding; A. Ding; A. Ding; et al. (Atmospheric Chemistry and Physics, 2019)
Aerosols can not only participate in fog formation by acting as condensation nuclei of droplets but also modify the meteorological conditions such as air temperature and moisture, planetary boundary layer height (PBLH) and regional circulation during haze events. The impact of aerosols on fog formation, yet to be revealed, can be critical in understanding and predicting fog–haze events. In this study, we used the Weather Research and Forecasting model coupled with Chemistry (WRF-Chem) to investigate a heavy fog event during a multiday intense haze pollution episode in early December 2013 in the Yangtze River Delta (YRD) region in eastern China. Using the WRF-Chem model, we conducted four parallel numerical experiments to evaluate the roles of aerosol–radiation interaction (ARI), aerosol–cloud interaction (ACI), black carbon (BC) and non-BC aerosols in the formation and maintenance of the heavy fog event. We find that only when the aerosols' feedback processes are considered can the model capture the haze pollution and the fog event well. And the effects of ARI during the fog–haze episode in early December 2013 played a dominant role, while the effects of ACI were negligible. Furthermore, our analyses show that BC was more important in inducing fog formation in the YRD region on 7 December than non-BC aerosols. The dome effect of BC leads to an increase in air moisture over the sea by reducing PBLH and weakening vertical mixing, thereby confining more water vapor to the near-surface layer. The strengthened daytime onshore flow by a cyclonic wind anomaly, induced by contrast temperature perturbation over land and sea, transported moister air to the YRD region, where the suppressed PBLH and weakened daytime vertical mixing maintained the high moisture level. Then heavy fog formed due to the surface cooling at night. This study highlights the importance of anthropogenic emissions in the formation of advection–radiation fog in the polluted coastal areas.